Eradicating Al-Qur'an Illiteracy of Prospective Primary School Teachers - Supriyadi, Tedi; Julia, J.; Iswara, Prana Dwija; Aeni, Ani Nur (Mimbar Sekolah Dasar, 2019)
Lack of students abilities in reading Al-Quran hampers the learning process of Islamic Religious Education (PAI Pendidikan Agama Islam) in universities. Ironically, this fundamentalism has not been able to be resolved at the previous level of education. Various methods of reading Al-Quran have been compiled, but in fact, there are still many students who have not been able to read Al-Quran. Hence, this research aims at analyzing the implementation of the TAHQIQ learning model in order to improve Al-Quran reading skills. This research employed the action research method. The research subjects were 360 prospective primary school teachers in one of the universities in Sumedang Regency, consisting of 130 male and 240 female prospective teachers. This research revealed that the TAHQIQ learning model was able to improve the students abilities in reading Al-Quran to reach the level of Jayyid in 12 meetings. Therefore, it can be concluded that the TAHQIQ learning model was able to eradicate students who were Al-Quran illiterate.